Evaluation of interventions on road traffic injuries in Peru: a qualitative approach - Huicho Luis; Adam Taghreed; Rosales Edmundo; Paca-Palao Ada; López Luis; Luna Diego; Miranda J Jaime (BMC, 2012)
Abstract Background Evaluation of interventions on road traffic injuries (RTI) going beyond the assessment of impact to include factors underlying success or failure is an important complement to standard impact evaluations. We report here how we used a qualitative approach to assess current interventions implemented to reduce RTIs in Peru. Methods We performed in-depth interviews with policymakers and technical officers involved in the implementation of RTI interventions to get their insight on design, implementation and evaluation aspects. We then conducted a workshop with key stakeholders to analyze the results of in-depth interviews, and to further discuss and identify key programmatic considerations when designing and implementing RTI interventions. We finally performed brainstorming sessions to assess potential system-wide effects of a selected intervention (Zero Tolerance), and to identify adaptation and redesign needs for this intervention. Results Key programmatic components were consistently identified that should be considered when designing and implementing RTI interventions. They include effective and sustained political commitment and planning; sufficient and sustained budget allocation; training, supervision, monitoring and evaluation of implemented policies; multisectoral participation; and strong governance and accountability. Brainstorming sessions revealed major negative effects of the selected intervention on various system building blocks. Conclusions Our approach revealed substantial caveats in current RTI interventions in Peru, and fundamental negative effects on several components of the sectors and systems involved. It also highlighted programmatic issues that should be applied to guarantee an effective implementation and evaluation of these policies. The findings from this study were discussed with key stakeholders for consideration in further designing and planning RTI control interventions in Peru.